THE INFLUENCE OF CHALLENGE STRESSORS AND JOB DEMAND ON CREATIVITY OF ONLINE RIDE-HAILING DRIVERS: MEDIATING ROLE OF WORK ENGAGEMENT - Utari Muthia Azzahra; Handrio Adhi Pradana; Andriyastuti Suratman (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2022)
This research intends to ascertain the impact of work engagement as mediatior that affect relationships between challenge stressors and job demand toward employee creativity. The sample size of 120 respondents in this quantitative study were online ride-hailing drivers from Go-Jek, Grab, Shopee-Food, and Maxim who were located across some major cities and regions in Indonesian. Purposive sampling is used to collect the required data for analysis, and Google Forms are used to distribute surveys and questionnaire in online fashion. The result shows that challenge stressors has a positive and significant influence on creativity and work engagement, as well as the impact of job demand on creativity and especially for work engagement is not significant, then mediation role of work engagement did not confirm this relationship. Moreover, work engagement mediates the relationship of challenge stressors toward creativity.